Genomewide Association Study Identifies Novel Genetic Loci That Modify Antiplatelet Effects and Pharmacokinetics of Clopidogrel. Issue 6 (9th February 2017) - Zhong, W‐P; Wu, H; Chen, J‐Y; Li, X‐X; Lin, H‐M; Zhang, B; Zhang, Z‐W; Ma, D‐L; Sun, S; Li, H‐P; Mai, L‐P; He, G‐D; et al.
Abstract : Genetic variants in the pharmacokinetic (PK) mechanism are the main underlying factors affecting the antiplatelet response to clopidogrel. Using a genomewide association study (GWAS) to identify new genetic loci that modify antiplatelet effects in Chinese patients with coronary heart disease, we identified novel variants in two transporter genes ( SLC14A2 rs12456693, ATP‐binding cassette [ ABC ] A1 rs2487032) and in N6AMT1 (rs2254638) associated with P2Y12 reaction unit (PRU) and plasma active metabolite (H4) concentration. These new variants dramatically improved the predictability of PRU variability to 37.7%. The associations between these loci and PK parameters of clopidogrel and H4 were observed in additional patients, and its function on the activation of clopidogrel was validated in liver S9 fractions ( P < 0.05). Rs2254638 was further identified to exert a marginal risk effect for major adverse cardiac events in an independent cohort. In conclusion, new genetic variants were systematically identified as risk factors for the reduced efficacy of clopidogrel treatment.